Proximate and Phytochemical Composition of Bajakah (Spatholobus littoralis Hassk) Extract and its Effect on Fasting Blood Glucose in STZ-HFD-Induced Diabetic Rats - Dara, Rizki Wulan; Lisyawati, Shanti; Febrinasari, Ratih Puspita (Media Publikasi Cendekia Indonesia, 2025)
The rising global prevalence of type 2 diabetes mellitus (T2DM) highlights the urgent need for plant-based therapeutic alternatives. Spatholobus littoralis Hassk, locally known as Bajakah, is a traditional medicinal plant from West Kalimantan, Indonesia, that is widely used by indigenous communities for regulating blood sugar levels. This study aimed to characterize the proximate and phytochemical composition of Bajakah wood extract and evaluate its antidiabetic potential in rats induced with a high-fat diet (HFD) and Streptozotocin (STZ). The extraction was performed using a 70% ethanol maceration method. Proximate analysis revealed low moisture (4.57%), ash (0.54%), total fat (0.81%), and protein (0.41%), with carbohydrates being the most abundant component (6.67%). Phytochemical screening using UV-Vis spectrophotometry identified total phenols (12.98%), flavonoids (1.16%), tannins (1.65%), and saponins (0.13%). The in vivo test on diabetic rats showed that the administration of Bajakah extract at a dose of 150 mg/kg body weight (BW) for 14 days significantly reduced fasting blood glucose levels from 279.46 ± 2.39 mg/dL to 115.62 ± 13.73 mg/dL (P= 0,028), corresponding to a 58,6% reduction. This reduction was greater than that of the positive control group, which was treated with Acarbose. The high content of phenolics and other bioactive compounds is strongly suggested to contribute to the antihyperglycemic effect through antioxidant mechanisms, inhibition of digestive enzymes, and enhancement of insulin sensitivity. This study these findings support the therapeutic potential of Bajakah wood extract from West Kalimantan as a complementary agent for management of T2DM.